EFFECT 0F HIGH AND COLD TEMPERATURE STORAGE PERIOD AND KIND OF WATER ON SUSPENSION STABILTY OF MALATHION AND METHOMYL INSECTICIDES - Nazar M .Al-Mallah (Mesopotamia Journal of Agriculture)
The Results of studying the effect of tropical and cold storage periods and kind of water (hard water.tap water. river water. Well water).on suspension stability of Malathion and Methomyl showed that the mean suspensibility percentage was influenced by the tropical storage period and that Malathion was affected more than Mithomyle and its suspensibility percentage reached 44.76% when stored for three months at 55c by using tap water .in comparison with 61.71% of control. The suspensibility percentage was influenced by the longivety of cold cold storage period .and reached 52.61% for Malathion WHEN stored for three months at 5c by using tap water compared with 62.16% of control . followed by Methomyle 80.14% when stored for three months at -5c using well water .in commparison with 88.06% of control .The well water showed more effect on the general mean of suspensibility percentage of Malathion and Methomyl which reached 57.39,.86.37% respectivley.